Ultrastrong and Highly Sensitive Fiber Microactuators Constructed by Force‐Reeled Silks - Lin, Shihui; Wang, Zhen; Chen, Xinyan; Ren, Jing; Ling, Shengjie (Advanced science, 2020)
Fiber microactuators are interesting in wide variety of emerging fields, including artificial muscles, biosensors, and wearable devices. In the present study, a robust, fast‐responsive, and humidity‐induced silk fiber microactuator is developed by integrating force‐reeling and yarn‐spinning techniques. The shape gradient, together with hierarchical rough surface, allows these silk fiber microactuators to respond rapidly to humidity. The silk fiber microactuator can reach maximum rotation speed of 6179.3° s−1 in 4.8 s. Such a response speed (1030 rotations per minute) is comparable with the most advanced microactuators. Moreover, this microactuator generates 2.1 W kg−1 of average actuation power, which is twice higher than fiber actuators constructed by cocoon silks. The actuating powers of silk fiber microactuators can be precisely programmed by controlling the number of fibers used. Lastly, theory predicts the observed performance merits of silk fiber microactuators toward inspiring the rational design of water‐induced microactuators. A new kind of robust and fast‐responsive silk microactuators, by integrating experimental and theoretical designs, are presented. These microactuators feature an ultrafast response speed for humidity change with performance that can compare with the most advanced microactuator systems.